Improving Students’ Interest in Learning Listening Skill Using Song Lyrics at the Eighth Grade of Madrasah Tsanawiyah (MTs.) Al-Badriyah Boarding School Sundak Rarang: Meningkatkan Minat Siswa Dalam Pembelajaran Keterampilan Menyimak Menggunakan Lirik Lagu di Kelas VIII Madrasah Tsanawiyah (MTs.) Pesantren Al-Badriyah Sundak Rarang - Hamidayani, Baiq Husnia (Pesantren Reviews, 2023)
The aim of this research is to improve students’ interest in learning listening skills by using song lyrics to know if there is any significant improvement during the learning process. Therefore, the methodology of this research is Classroom Action Research (CAR). It was conducted in two cycles. Each cycle consists of planning, action, observation, and reflection. The data was obtained from tests and observation. The test was used to measure students’ interest in learning listening skill by listening to song lyrics, and observation used to get additional information about the students’ reflection toward the learning activities by using song lyrics. From the result of the research, the researcher found that teaching listening through song lyrics can improve students’ interest in learning listening skills. The findings show that the students’ score in cycle 2 is higher than score test in cycle 1. The calculation leads to the results of cycle 1 which in the first cycle students’ mean score was 64,21 and in the second cycle was 94,73. This means that in cycle 1 and cycle 2, the interest of students was improved. During the learning process, the students were enthusiastic, active, and attentive in listening English words from song lyrics. Overall, the findings showed that teaching listening using song lyrics was an appropriate media to improve students’ interest in learning listening skills.